2007
DOI: 10.1055/s-2006-924365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hemopure™ on Maximal Oxygen Uptake and Endurance Performance in Healthy Humans

Abstract: Haemoglobin-based oxygen carriers (HBOCs) such as Hemopure are touted as a tenable substitute for red blood cells and therefore potential doping agents, although the mechanisms of oxygen transport of HBOCs are incompletely understood. We investigated whether infusion of Hemopure increased maximal oxygen uptake (V.O 2max) and endurance performance in healthy subjects. Twelve male subjects performed two 4-minute submaximal exercise bouts equivalent to 60 % and 75 % of V.O (2max) on a cycle ergometer, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The results of the trial indicated that Hemopure® did not increase maximal O 2 uptake (VO 2max ). Hemopure® also increased the diastolic (∼8 mm Hg) ( P = 0.046) and mean (∼7 mm Hg) blood pressure 73…”
Section: Non‐site‐specific Hboc Designmentioning
confidence: 91%
“…The results of the trial indicated that Hemopure® did not increase maximal O 2 uptake (VO 2max ). Hemopure® also increased the diastolic (∼8 mm Hg) ( P = 0.046) and mean (∼7 mm Hg) blood pressure 73…”
Section: Non‐site‐specific Hboc Designmentioning
confidence: 91%
“…The metabolism of HBOC-201 in men and women seems to be similar and metabolized by the mononuclear phagocyte system (MPS) to bilirubin. Ashenden et al reported that after healthy male subjects were infused with HBOC-201, the blood oxygen-carrying capacity was improved (46). HBOC-201 has been shown to be effective in increasing oxygen extraction and delivery to peripheral and central organs and improving tissue oxygenation in studies related to isovolumetric hemodilution (47)(48)(49)(50)(51).…”
Section: Properties Of Hboc-201mentioning
confidence: 99%
“…Hemopure V V R also increased the diastolic ($8 mm Hg) (P ¼ 0.046) and mean ($7 mm Hg) blood pressure. 73 Oxyglobin V V R (HBOC-301) is another glutaraldehyde-polymerized bHb manufactured by Biopure for veterinary use. 74 HBOC-301 was approved by the FDA and is commercially available for use in treating canine anemia.…”
Section: Non-site-specific Hboc Designmentioning
confidence: 99%